Asymptotic-Preserving methods and multiscale models for plasma physics - Degond,PAA; Deluzet,F (Journal of Computational Physics, 2017)
The purpose of the present paper is to provide an overview of Asymptotic-Preserving methods for multiscale plasma simulations by addressing three sin-gular perturbation problems. First, the quasi-neutral limit of fluid and kineticmodels is investigated in the framework of non magnetized aswell as magne-tized plasmas. Second, the drift limit for fluid descriptions of thermal plasmasunder large magnetic fields is addressed. Finally efficient numerical resolutionsof anisotropic elliptic or diffusion equations arising in magnetized plasma simu-lation are reviewed.